Prediction of Heart Diseases (PHDs) based onMulti-Classifiers (International Journal of Food and Nutritional Sciences, 2019)
Now a days, heart disease is one among the most complicated issues and globally manypeople Effected from this disease. A major obstacle to clinical data analyticsis the disease'sprediction. In time identification of disease is crucial to save patient, so health industry collectdata from across world and transforms huge amounts of raw data into useful information.With the help of this useful information, we executed various machine learning algorithms topredict the heart disease